IMPLEMENTASI GENETIC FUZZY SYSTEM UNTUK MENGIDENTIFIKASI HASIL CURIAN KENDARAAN BERMOTOR DI POLDA LAMPUNG - Arie Setya Putra; Ochi Marshella Febriani; Bobby Bachry (Institut Informatika dan Bisnis Darmajaya, 2018)
The development of this technology is very fast, one of the media that utilizes technology such as application DPB Ranmor 2.0 in Polda Lampung That’s in Play Store. In This Case will be solved by genetic Fuzzy System, most notably the development of the Genetic Fuzzy tree Methodology, have allowed fuzzy logic based Artificial Intellegence to be developed Application that can be applied to incredibly complex problem. The Ability of Information Retrieval to have extreme performance and computational efficiency as well as to be robust to uncertainties and randomness.The concept will be adopted for case Criminal in Lampung. Thief and Criminal in lampung its more completed, thiefs will sell his results of crime anywhere DPB Ranmor its one of Application will be pushed in results criminal ( ranmor ). This methodology is an ideal solution to a very wide array of problems.Keywords : Genetic Fuzzy Systems; Artificial Intellegence; Informasi retrieval; Aplikasi